2017
DOI: 10.15640/jaes.v6n2a9
|View full text |Cite
|
Sign up to set email alerts
|

Les Déterminants De L’efficience Technique Des Riziculteurs De L’office Du Niger Au Mali The Office Niger Rice Farmers’ Technical Efficiency Determinants in Mali

Abstract: The purpose of this study was to determine the level of technical efficiency score and to analyze its determinants in the Office Niger area in Mali. The data used are a cross section of producers collected in April 2014. The final sample is made of 130 observations. A Cobb-Douglas model is used to fit the data using frontier 4.1 and Stata 14 software. Our investigations found out that the rice cultivation at the Office Niger evolves in a non-variable returns to scale framework. The average technical efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…The increase in production is usually achieved in Sub-Saharan Africa through the increase in land cultivated. This result confirms the finding of Coulibaly et al (2017) and Audibert (1997) who found that rice production highly depended on changes in the land at "office du Niger" in Mali. This result also supports the findings of Koirala et al (2014).…”
Section: Estimation Of Parameters Of the Stochastic Frontier And Metasupporting
confidence: 91%
See 4 more Smart Citations
“…The increase in production is usually achieved in Sub-Saharan Africa through the increase in land cultivated. This result confirms the finding of Coulibaly et al (2017) and Audibert (1997) who found that rice production highly depended on changes in the land at "office du Niger" in Mali. This result also supports the findings of Koirala et al (2014).…”
Section: Estimation Of Parameters Of the Stochastic Frontier And Metasupporting
confidence: 91%
“…Cereals are the staple food in Mali. Particularly, rice remains the most consumed representing about 30% of total cereal consumption (Coulibaly, Savadogo, & Diakité, 2017). The local consumption per capita has increased from 69.7 kg/person/year in 2010 to 105 kg/person/year in 2013 (Van Oort et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations